The relationship between oxytocin and antisocial behaviors - Tan, Gary Ye Chao (Nanyang Technological University, 2022)
Social behaviors are behaviors where two or more individuals interact with each other. Oxytocin is a neurohormone that has been associated with social behavior. Antisocial behaviors are acts detrimental to the self and others affected by the person’s actions. The relationship between oxytocin and antisocial behaviors has been mixed. In this paper, a meta-analysis is conducted to understand the relationship between oxytocin and antisocial behaviors. A total of 31 independent effect sizes were calculated from 27 studies involving 2019 participants. These effects sizes were obtained from both interventional and observational studies. Overall, the fixed effect and random effects models produced non-significant summary effect sizes (SMD = -0.03, p = .518 and SMD = -0.06, p = .589 respectively), suggesting a lack of relationship between oxytocin and antisocial behaviors. Heterogeneity tests revealed that the effects sizes were non-homogenous and warranted additional analyses to be conducted. Moderator analyses revealed that higher oxytocin levels were negatively associated with conduct problems (SMD = -0.49, p = .033). A significant negative correlation was found of the relationship between oxytocin and antisocial behaviors only in children (SMD = -0.42, p = .044). Higher oxytocin was significantly associated with lower antisocial behavior in the studies conducted in Turkey (SMD = -0.79, p = .000). The results highlight the importance of investigating moderators in oxytocin-antisocial behavior studies and that the relationship between oxytocin and antisocial behaviors is indirect.